2020
DOI: 10.3390/horticulturae6040089
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Metamitron under Different Relative Humidity Conditions on the Fruit Abscission of Malus domestica Borkh. Cultivars

Abstract: Metamitron is an apple (Malus domestica Borkh.) fruit thinner that acts by reducing the photosynthetic capacity of trees. Relative humidity may influence thinning efficacy; however, the broadness of this effect is not yet fully understood. Trials were set in Sint-Truiden (Belgium) in 2018 and Lleida and Girona (Spain) in 2019, using 4-year-old cvs. Braeburn and Elstar trees in Belgium, and 16-year-old cv. Golden Reinders trees in Spain. Four treatments were implemented at the stage of 12–14 mm fruit diameter: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…In Sint-Truiden, MET+HNT showed a significantly lower P n at 2 DAS and incomplete recovery at 10 DAS, explained by the increase in metamitron absorption verified under these conditions. Metamitron application also reduced g s which is in line with a study developed by Rosa et al (2020) in "Golden" and "Gala" trees, after the application of 247.5 ppm of metamitron.…”
Section: Metamitron Concentration In the Leaves And Effect On Gas Exc...supporting
confidence: 88%
See 2 more Smart Citations
“…In Sint-Truiden, MET+HNT showed a significantly lower P n at 2 DAS and incomplete recovery at 10 DAS, explained by the increase in metamitron absorption verified under these conditions. Metamitron application also reduced g s which is in line with a study developed by Rosa et al (2020) in "Golden" and "Gala" trees, after the application of 247.5 ppm of metamitron.…”
Section: Metamitron Concentration In the Leaves And Effect On Gas Exc...supporting
confidence: 88%
“…The strong P n reduction caused by metamitron would likely limit photoassimilates production, which is in concordance with the lower sugar content observed in MET treatment in both years. A study developed by Rosa et al (2020) in three apple cultivars shows significant decreases in sucrose, sorbitol and total sugars between 20-50% five days after the application of 247.5 ppm of metamitron. In mandarin, Stander et al (2018) reported a 12% shortage in total sugars one day after spraying 300 ppm of metamitron, which persisted until 7 DAS.…”
Section: Effect On Non-structural Carbohydratesmentioning
confidence: 99%
See 1 more Smart Citation
“…In New York State, it is common to have cloudy days during the spring period. These cloudy days cause shortages of carbohydrates required to support fruit growth [37]. Our results suggest that cloudy days (total daily solar radiation less than 16 MJ m −2 day −1 ) after metamitron application increased fruit drop.…”
Section: Discussionmentioning
confidence: 68%